Characteristics and prognostic implications of high-risk HPV-associated hypopharyngeal cancers. - Young-Hoon Joo; Youn-Soo Lee; Kwang-Jae Cho; Jun-Ook Park; In-Chul Nam; Chung-Soo Kim; Sang-Yeon Kim; Min-Sik Kim (PLoS ONE, 2013)
BACKGROUND: High-risk human papillomavirus (HPV) is an oncogenic virus that causes oropharyngeal cancers, and it has a favorable outcome after the treatment. Unlike in oropharyngeal cancer, the prevalence and role of high-risk HPV in the etiology of hypopharyngeal squamous cell carcinoma (HPSCC) is uncertain. OBJECTIVE: The aim of the present study was to evaluate the effect and prognostic significance of high-risk HPV in patients with HPSCC. METHODS: The study included 64 subjects with HPSCC who underwent radical surgery with or without radiation-based adjuvant therapy. Primary tumor sites were the pyriform sinus in 42 patients, posterior pharyngeal wall in 19 patients, and postcricoid area in 3 patients. High-risk HPV in situ hybridization was performed to detect HPV infection. RESULTS: The positive rate of high-risk HPV in situ hybridization was 10.9% (7/64). There was a significant difference in the fraction of positive high-risk HPV among pyriform sinus cancer (16.7%), posterior pharyngeal wall cancer (0%), and postcricoid area cancer (0%) (p = 0.042). The laryngoscopic examination revealed a granulomatous and exophytic appearance in 85.7% (6/7) of patients with high-risk HPV-positive pyriform sinus cancer, but in only 31.4% (11/35) of patients with high-risk HPV-negative pyriform sinus cancer (p = 0.012). Significant correlations were found between positive high-risk HPV and younger age (p = 0.050) and non-smoking status (p = 0.017). HPV-positive patients had a significantly better disease-free survival (p = 0.026) and disease-specific survival (p = 0.047) than HPV-negative patients. CONCLUSIONS: High-risk HPV infection is significantly related to pyriform sinus cancer in patients with HPSCC.